Antena de microfita com substrato metamaterial - Aquino, Manoel do Bonfim Lins de (2008)
This paper presents a theoretical and numerical analysis of the parameters of a rectangular microstrip antenna with metamaterial substrate. The metamaterial (MTM) theory was applied along with Transverse Transmission Line (LTT) method to characterize substrate quantities and obtain the general equations of the electromagnetic fields. A study on metamaterial theory was conducted to obtain the constructive parameters, which were characterized through permittivity and permeability tensors to arrive at a set of electromagnetic equations. Electromagnetic principes are used to obtained parameters such as complex resonance frequency, bandwidth and radiation pattern were then obtained. Different metamaterial and antenna configurations were simulated to miniaturize them physically and increase their bandwidth, the results of which are shown through graphics. The theoretical computational analysis of this work proved to be accurate when compared to other studies, and may be used for other metamaterial devices. Conclusions and suggestions for future work are also proposed